Pyroelectrical model for intracloud lightning - Falcón, Nelson; Quintero, Amilkar (Ciencia)
We present a theoretical microphysical model of thundercloud electrification that incorporates the influence of an aerosol with electrical self-polarization (pyroelectric), like methane. We estimate the water and methane dipole contribution to the internal electric field and calculate the associated capacitance for the cloudy cell, using the telluric capacitor approach, with methane concentration lower than the air composition. We obtain that the water contribution to the internal electric field due to the electrical displacement vector generated by the atmospheric electric field of the Earth, is not enough to produce a typical discharge; the methane increases the electric field inside thunderclouds and facilitates the electrical charge generation and separation process. Applications in Titan Lightning activity and lightning of the Catatumbo River are suggested.